2017
DOI: 10.1038/s41551-017-0117-6
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound-triggered local anaesthesia

Abstract: On-demand relief of local pain would allow patients to control the timing, intensity and duration of nerve block in a safe and non-invasive manner. Ultrasound would be a suitable trigger for such a system, as it is in common clinical use and can penetrate deeply into the body. Here, we demonstrate that ultrasound-triggered delivery of an anaesthetic from liposomes allows the timing, intensity and duration of nerve block to be controlled by ultrasound parameters. On insonation, the encapsulated sonosensitizer p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
121
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 116 publications
(122 citation statements)
references
References 78 publications
(102 reference statements)
0
121
0
1
Order By: Relevance
“…Use of ultrasound with lower frequency and power improves the cavitation and concomitant biological effect (Hu et al, ; Qian, Zheng, & Chen, ). Multiple studies have shown that some sensitizers can be efficiently activated by ultrasound and generates cytotoxic ROS (Giuntini et al, ; Li et al, ; Rwei et al, ). Recently, a lot of sonosensitizers has been applied in SDT, including TiO 2 , chlorin, phthalocyanines and photofrin (Osaki et al, ; Rwei et al, ; Xu et al, ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Use of ultrasound with lower frequency and power improves the cavitation and concomitant biological effect (Hu et al, ; Qian, Zheng, & Chen, ). Multiple studies have shown that some sensitizers can be efficiently activated by ultrasound and generates cytotoxic ROS (Giuntini et al, ; Li et al, ; Rwei et al, ). Recently, a lot of sonosensitizers has been applied in SDT, including TiO 2 , chlorin, phthalocyanines and photofrin (Osaki et al, ; Rwei et al, ; Xu et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Multiple studies have shown that some sensitizers can be efficiently activated by ultrasound and generates cytotoxic ROS (Giuntini et al, ; Li et al, ; Rwei et al, ). Recently, a lot of sonosensitizers has been applied in SDT, including TiO 2 , chlorin, phthalocyanines and photofrin (Osaki et al, ; Rwei et al, ; Xu et al, ). Among them, hematoporphyrin monomethyl ether (HMME), a newly approved sonosensitizer by SFDA, displays good potential in the application of SDT (Li, Song, Xu, Huang, & Yue, ; Nelson et al, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…More and higher intensity shockwave treatment induced more and larger areas of bubbles in the phantoms, implying more cavitation activity leading to larger areas of BBB opening and tissue injury (i.e., red blood cells extravasation, apoptosis and glia cell infiltration). The extensive red blood cell extravasation produced by the addition of UCA is probably due to the high peak negative pressure of the shockwaves and strong cavitation effect in the rat brains (see Table 1 for detailed parameters) 24–26 .
Figure 9Bubbles generated after 0, 50, and 100 shocks at PRF 5 Hz and intensity levels of 10 and 5.
…”
Section: Discussionmentioning
confidence: 99%
“…Shockwaves are well known to produce cavitation 24 , which is believed to be the major mechanism responsible for opening the BBB by HIFU 25,26 . Furthermore, focused shockwaves operate at a lower frequency than ultrasound, thus offering better penetration.…”
Section: Introductionmentioning
confidence: 99%